Study of the antibacterial activity in the gas phase of a chemical formulation for household waste management. (21st December 2014) - Motta, O.; Zarrella, I.; Cucciniello, R.; Vigliotta, G.; Proto, A.
Abstract The aim of this study was to formulate a product (microbicide mixture) that could slow down the bacterial proliferation during the storage of household waste. We used harmless and natural components, known for their antimicrobial properties, in the liquid phase at direct contact with the microbes. The antimicrobial activity of the microbicide mixture formulated was evaluated over a range of concentration in two types of tests, in the liquid and in the gas phase. Once the efficacy of antimicrobial agent in the liquid phase in direct contact with the microbe (Escherichia coli) was confirmed, we adopted a new approach to evaluate the effect of the vapour phase both on the microbes' growth and on its duration. Here, we show that the perfect combination that gives rise to an antimicrobial mixture useful to control microbial growth (Staphylococcus aureus, Escherichia coli, Debaryomyces hansenii or Penicillium citrinum) up to 4 weeks is the one between more volatile agents (2‐propanol and limonene) and a less volatile agent (cinnamaldehyde). The pleasant smell as well as the synergic antibacterial and antifungal function of the natural components of this mixture makes it attractive in domestic waste management. Significance and Impact of the Study The novelty of this work is two‐fold: on the one hand, to test various antimicrobial components of different volatility in a single microbicide mixture, and on the other, to study antimicrobial activity in the gas phase, other than the liquid phase. While previous authors tested the components individually as antimicrobial agents in the liquid phase at direct contact with the microbes, we tested them altogether as a mixture both in the liquid and in gas phase. The aim of this study was to disinfect small environments, such as garbage containers, by favouring the diffusion of the vapour phase to avoid the growth of microbes. This study proposes a new approach in the management and storage of household waste by inhibiting bacterial proliferation in the garbage can.